2010
DOI: 10.1002/hep.23311
|View full text |Cite|
|
Sign up to set email alerts
|

Expression and Functional Significance of Twist1 in Hepatocellular Carcinoma: Its Role in Vasculogenic Mimicry

Abstract: The up-regulation and nuclear relocation of epithelial-mesenchymal transition (EMT) regulator Twist1 have been implicated in the tumor invasion and metastasis of human hepatocellular carcinoma (HCC). The term vasculogenic mimicry (VM) refers to the unique capability of aggressive tumor cells to mimic the pattern of embryonic vasculogenic networks. However, the relationship between Twist1 and VM formation is not clear. In this study, we explored HCC as a VM and EMT model in order to investigate the role of Twis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
330
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(351 citation statements)
references
References 32 publications
18
330
2
1
Order By: Relevance
“…In addition, similar structures have been reported by several groups in other tumors using H&E staining and CD31/ CD34-PAS double staining (15,17,(41)(42)(43). VM was present in 18 of 71 (25.4%) cases by using H&E and CD31-PAS double staining, which is different from other tumors, such as ovarian carcinoma (36.4%) (13), breast cancer (7.9%) (12) and HCC (19%) (44). However, our results were similar to another report, such as LSCC (21.67%) (15).…”
Section: Discussionsupporting
confidence: 84%
“…In addition, similar structures have been reported by several groups in other tumors using H&E staining and CD31/ CD34-PAS double staining (15,17,(41)(42)(43). VM was present in 18 of 71 (25.4%) cases by using H&E and CD31-PAS double staining, which is different from other tumors, such as ovarian carcinoma (36.4%) (13), breast cancer (7.9%) (12) and HCC (19%) (44). However, our results were similar to another report, such as LSCC (21.67%) (15).…”
Section: Discussionsupporting
confidence: 84%
“…This observation is in drastic contrast to the traditional angiogenesis process contributed by surrounding endothelial progenitors that are triggered by cytokines and pro-angiogenic factors secreted from tumour-associated macrophages/ neutrophils and tumour-associated fibroblasts 2,3 . Induction of tumour-derived endothelial differentiation by Twist1 is different from the vasculogenic mimicry mechanism 33,34 , which does not activate endothelial markers and may represent an incomplete differentiation towards the endothelial lineage. This induction of endothelial differentiation may be critical for tumour progression and metastasis since knockdown of either Jagged1 or KLF4 significantly decreases the in vitro or in vivo metastatic activity induced by Twist1 ( Fig.…”
Section: Oecm1-twist1mentioning
confidence: 81%
“…The latter agent is not the only adhesive molecule, but it may lead to induction of vascular cascade [23]. Earlier, Sun and co-workers [81] and Liu and co-workers [52] indicated a strong connection between EMT and VM. It is suggested that as a result of VM connection with EMT, tumor cells acquire features typical for stem cells phenotype (CSCs) with ability to invasion and migration [28].…”
Section: Vasculogenic Mimicry Of Tumorsmentioning
confidence: 99%
“…An increase of VM density is connected with the increase of PGCCs amount. [10,57,92] mechanism of formation independent of VEGF, EMT contribution [52,54,57,81] interaction with ECM increase of MMPs activity and ECM remodeling [50,60] phenotype/ cell plasticity expression of stem cell multipotent phenotype (Sox-2, TWIST-1, CD133/CD44) with ability to ECs differentiation at the same time [46,68,74,84,85] tumor invasiveness and metastasis high tumor progresion and aggressiveness [50,63] prognosis for patient adverse prognostic factor, shorter survival of patient [8,50,51] Final classification of vessel-like structures needs usually more studies towards amplification of EGFR gene, which is often observed in tumor cells derived from epithelial tissue [26].…”
Section: Vasculogenic Mimicry Of Tumorsmentioning
confidence: 99%